2009
DOI: 10.1098/rspb.2009.1452
|View full text |Cite
|
Sign up to set email alerts
|

High stimulus specificity characterizes anti-predator habituation under natural conditions

Abstract: Habituation is one of the most fundamental learning processes that allow animals to adapt to dynamic environments. It is ubiquitous and often thought of as a simple form of non-associative learning. Very little is known, though, about the rules that govern habituation and their significance under natural conditions. Questions about how animals incorporate habituation into their daily behaviour and how they can assure only to habituate to non-relevant stimuli are still unanswered. Animals under threat of predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
4
49
0
Order By: Relevance
“…The waning of the escape response to repeated presentations of a VDS and the ability to distinguish this stimulus from a slightly different one, described in our laboratory studies with Chasmagnathus, has been recently found to be present in the natural environment of the fiddler crab Uca vomeris (Hemmi and Merkle, 2009). As with Chasmagnathus, fiddler crabs were found to reduce their escape response to the repeated approach of a dummy predator, and the behavioral change proved to be stimulus specific and not retinotopic.…”
Section: Discussionmentioning
confidence: 75%
“…The waning of the escape response to repeated presentations of a VDS and the ability to distinguish this stimulus from a slightly different one, described in our laboratory studies with Chasmagnathus, has been recently found to be present in the natural environment of the fiddler crab Uca vomeris (Hemmi and Merkle, 2009). As with Chasmagnathus, fiddler crabs were found to reduce their escape response to the repeated approach of a dummy predator, and the behavioral change proved to be stimulus specific and not retinotopic.…”
Section: Discussionmentioning
confidence: 75%
“…For both species, field research has underscored the critical role of the burrow in predator avoidance (Fathala et al, 2010a,b;Hemmi, 2005a;Hemmi and Zeil, 2003a) and has shown that the escape response habituates (Hemmi and Merkle, 2009;Raderschall et al, 2011;Tomsic et al, 1993Tomsic et al, , 1998. There are, however, differences between the observed behaviours that are significant.…”
Section: Introductionmentioning
confidence: 62%
“…There are, however, differences between the observed behaviours that are significant. These differences are difficult to interpret because studies on the escape behaviour of N. granulata were predominantly done in the laboratory, in combination with neurophysiological analyses (Berón de Astrada et al, 2013;Oliva et al, 2007;Tomsic, 2008, 2011;Tomsic et al, 2003), whereas the majority of studies on U. vomeris have been carried out in the field (Hemmi, 2005a,b;Hemmi and Merkle, 2009;Hemmi and Pfeil, 2010;Smolka et al, 2012Smolka et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Models were selected by sequentially fitting parameters and including those parameters that reached significance at a 5% level when added to the final model. Because burrow distance (the distance between a crab and its burrow at the time of response) and track distance (the distance between a crab and the closest point of the dummy track) are known to be important predictors of response distance (Hemmi, 2005a;Hemmi, 2005b;Hemmi and Merkle, 2009;Hemmi and Pfeil, 2010;Raderschall et al, 2011), they were included in all models even if they did not reach significance. This was the case in two instances (see Table1), but it did not change the significance of other main effects and never changed the estimate of effect sizes by more than 7%.…”
Section: Methodsmentioning
confidence: 99%
“…Crabs initiated their home-runs much earlier in response to a flickering dummy than to either a black (Hemmi, 2005a;Hemmi, 2005b;Hemmi and Merkle, 2009;Hemmi and Pfeil, 2010) or a white dummy, used here as an intensity control (Table1, Fig. 2A,B).…”
Section: Experiments 1 and 2: Flicker Triggers Earlier Home-runsmentioning
confidence: 99%